Vertical Distribution of Zooplankton in Eastern Lancaster Sound and Western Baffin Bay, July-October 1978 - Buchanan, Robert A.; Sekerak, Aaron D. (ARCTIC, 1982)
Zooplankton samples (n=150) collected from 23 July to 10 October 1978 at 19 oceanographic stations were analyzed for species composition, abundance, biomass and vertical distribution. Sampling was by closing nets hauled vertically at five depth intervals between 0 and 1900 m. At least 116 species were present in the macro-zooplankton of the study area. Species not previously reported from the area included the copepods Spinocalanus horridus, Chiridiella reducta, Derjuginia tolli, Neoscolecithrix farrani?, Pachyptilus pacificus, Haloptilus longicirrus?, Mormonilla polaris, and Monstrilla longicirrus?. In addition, small numbers of the previously undescribed adult male stages of the copepods Aetideopsis multiserrata and A. rostrata were found. Three copepod species that appear to be new to science were also collected. The high numbers of species, new records for the area, and previously undescribed species or stages collected reflect the relatively intensive sampling, particularly in deep water. In general, the zooplankton was numerically dominated by copepods, particularly the calanoids Calanus glacialis, C. hyperboreus, Pseudocalanus minutus, Metridia longa and Microcalanus spp. and the cyclopoid Oithona similis. Most of these species (exceptions: Metridia langa and Microcalanus spp.) were most abundant in the upper 50 m: total zooplankton numbers were also greatest there. However, one or more stages of each of these copepod species, except P. minutus, were present in depths as great as 1900 m. Factor analysis identified 10 zooplankton assemblages. Of these, two were virtually restricted to the upper 50 m, two were mainly in the upper 50 m but were also found throughout the water column, five were primarily deep water groups (one almost entirely restricted to deep water), and one was primarily an intermediate depth group.Key words: zooplankton, vertical distribution, Baffin Bay, Lancaster Sound, species composition, abundance, biomass Mots clés: zooplancton, distribution verticale, Baie de Baffin, Détroit de ...